2004
DOI: 10.1089/107632704323061843
|View full text |Cite
|
Sign up to set email alerts
|

Laser Printing of Pluripotent Embryonal Carcinoma Cells

Abstract: A technique by which to print patterns and multilayers of scaffolding and living cells could be used in tissue engineering to fabricate tissue constructs with cells, materials, and chemical diversity at the micron scale. We describe here studies using a laser forward transfer technology to print single-layer patterns of pluripotent murine embryonal carcinoma cells. This report focuses on verifying cell viability and functionality as well as the ability to differentiate cells after laser transfer. We find that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
164
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 269 publications
(169 citation statements)
references
References 33 publications
4
164
0
1
Order By: Relevance
“…LIFT is an established technique for cell deposition, with postprinting cell viability reaching > 95% [40,41]. Furthermore, previous studies showed that cell suspensions could withstand laser-induced acceleration and deceleration of the order of 10 6 −10 7 g and authors speculated that only the cells at the front of the jet were damaged [42,43]. By analogy, our laser-assisted system could potentially be viable for sensitive cell-seeded liquids as we estimate from time-resolved imaging that the maximum deceleration at impact is of the order of 10 6 g.…”
Section: Application To Particle Deliverymentioning
confidence: 99%
“…LIFT is an established technique for cell deposition, with postprinting cell viability reaching > 95% [40,41]. Furthermore, previous studies showed that cell suspensions could withstand laser-induced acceleration and deceleration of the order of 10 6 −10 7 g and authors speculated that only the cells at the front of the jet were damaged [42,43]. By analogy, our laser-assisted system could potentially be viable for sensitive cell-seeded liquids as we estimate from time-resolved imaging that the maximum deceleration at impact is of the order of 10 6 g.…”
Section: Application To Particle Deliverymentioning
confidence: 99%
“…[67][68][69] The repetition rate of the laser (5 kHz) has showed high cell density (10 8 cells/mL), high-speed (200 mm/s), and highresolution (10 lm) patterning with multiple cell seeding on the scaffolds. 21 Gaebel et al compared the benefit of LIFT-based versus non-LIFT-based tissue engineered cardiac patches for the potential treatment of myocardial infarction.…”
Section: Biomaterials Printing Using Laser Induced Forward Transfermentioning
confidence: 99%
“…Further work enhanced the cell printing capabilities, showing that various cell types including human osteosarcoma and rat cardiac cells (Barron et al 2004b, Ringeisen et al 2004, could be printed with viability approaching 100% at near single-cell resolution using Matrigel™ as the absorptive layer. At the same time, this group developed the improved BioLP™ approach in an attempt to limit direct interaction between the laser and sensitive biomaterials (Barron et al 2004a).…”
Section: Current Progress Chrisey Et Al First Demonstrated the Maplementioning
confidence: 99%